The 1826 Ancaster Tar and Feathers Outrage: Three Defendants’ Perspectives - Petty, Ross (Ontario History)

(untitled) (The Ontario Historical Society, 2022)
Around midnight on 3-4 June 1826, Gore clerk of the peace George Rolph was attacked by a mob, dragged from his home, threatened with bodily harm, and tarred and feathered. He was accused of adultery with a live-in servant. Since Rolph was the brother of reform advocate John Rolph, the attack and related legal proceedings drew international attention and the civil trial was packed “almost to suffocation.” This outrage remained in the public eye for over two years as Rolph brothers sought justice and as other outrages occurred. This article examines the social background and politics of the outrage and the subsequent legal challenges from the perspectives of the three original defendants in the trial. It argues that personal, non-political factors were more significant motivations than previously recognized. This is the first paper to examine the perspectives of the three defendants.